Impact Of Emotional Intelligence And Parenting Style (Democratic) On The Performance Of Bilingual Chemistry Learning - Fitriah Khoirunnisa; Prof. Madya Aziz Bin Nordin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji, 2013)
The purpose of this study was to examine the relationship between students’ emotional intelligence and students’ democratic parenting style on the bilingual learning achievement of chemistry. This study was conducted on 159 students in the second class of International Pioneering School (RSBI), namely Senior High School 1 and 10, Samarinda, East Kalimantan, selected randomly. Questionnaires given to the students were related to students’ demographics, emotional intelligence and pattern of parental upbringing of students. The data were analyzed by using the Statistics Package for the Social Sciences (SPSS Version 17.0) to get the value of the Pearson’s Correlation. The analysis showed that there was a positive relationship between the students’ democratic parenting style with the students’ emotional intelligence in learning of bilingual chemistry subject (r = 0.289); there was a positive relationship between the learning achievement of bilingual chemistry with democratic parenting style (r = 0.106); there was positive relationship between students’ emotional intelligence with the learning achievement of bilingual chemistry (r = 0.112). Therefore, this study is expected to be the basis for teachers to develop effective learning process by building on students' emotional intelligence elements. In addition, parents can also apply a democratic parenting style to students at home. So that the merger of these two elements can enhance the results of students’ bilingual in chemistry subject.